Intimate partner sexual violence during pregnancy and its associated factors in Northwest Ethiopian women - Azene, Zelalem Nigussie; Merid, Mehari Woldemariam; Taddese, Asefa Adimasu; Andualem, Zewudu; Amare, Nakachew Sewnet; Taye, Birhan Tsegaw (Frontiers in Sociology, 2023)
Background: Violence against women is a global problem. In pregnant women, it is a particular concern as a virtue of the additional risks to the unborn child. Of different acts of violence, sexual violence shares the major contribution that results in short and long-term physical, sexual, reproductive, and mental health problems of pregnant women. Little is known about sexual violence during pregnancy in Ethiopia. Objective: this study aimed to assess the proportion and factors associated with intimate partners’ sexual violence against pregnant women in Northwest Ethiopia. Methods: A cross-sectional study was conducted among 409 pregnant women in Debre Markos town from March to April 2018. The study participants were selected using a systematic random sampling technique. A pre-tested and validated questionnaire was used. Binary logistic regression analyses were done to identify associated factors and the adjusted odds ratio (AOR) with its 95 % confidence interval (CI) at a p-value of <0.05 was used to declare a significant association. Result: Of 409 pregnant women, 19.8% have experienced sexual violence by their intimate partner during their current pregnancy. Accordingly, the major intimate partner sexual violence during pregnancy was having unwanted sexual intercourse due to fear from the partner (13.4%), being forced to do something sexual that is degrading or humiliating (13.0%), and being physically forced to have sexual intercourse (9.8%). Living with her partner/husband (AOR: 3.73, 95% CI: 1.30, 10.69), uneducated educational status of partner (AOR: 2.43, 95% CI: 1.06, 5.56), and frequency of alcohol consumption (AOR: 3.20, 95% CI: 1.24, 8.26) were factors associated with increased occurrence of intimate partner sexual violence during pregnancy. Conclusion: The proportion of sexual violence against pregnant women by their intimate partner(s) was found to be common in our study. Socio-demographic and behavioral-related factors were risk factors for sexual violence. As a result, preventive strategies and interventions centering on the empowerment of those facing the greatest barriers to reproductive freedom require a shift from traditional ways of thinking.